Investigating the Impact of the Snowball Throwing Cooperative Learning Approach on Elementary Students’ Social Studies Achievement in Makassar - Muhris , Irwan Setiawan; Idham , Afif Zuhdy; Taufik, Taufik (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
This study investigates the effect of the Snowball Throwing cooperative learning model on students’ learning outcomes in Social Studies (IPS) among fifth-grade students at SD Negeri Tamalanrea, Makassar, Indonesia. The research employed a true experimental design using the posttest-only control group design. The population comprised 325 students, and a total of 64 students were randomly selected as samples, divided into experimental and control groups. The experimental group received instruction through the Snowball Throwing model, while the control group was taught using conventional methods such as lectures and assignments. Data were collected through learning outcome tests and observation sheets, then analysed using descriptive and inferential statistics with SPSS. The results revealed that students in the experimental group achieved significantly higher posttest scores compared to those in the control group (p < 0.05). This finding indicates that the Snowball Throwing cooperative learning model effectively enhances students’ engagement and academic performance in Social Studies. The study concludes that applying interactive and student-cantered learning models can improve conceptual understanding and social skills among elementary school learners.